2016
DOI: 10.1002/ghg.1637
|View full text |Cite
|
Sign up to set email alerts
|

A modified true triaxial apparatus for measuring mechanical properties of sandstone coupled with CO2‐H2O biphase fluid

Abstract: Mechanical behaviors of rock under biphase or multiphase fluids conditions are key scientific issues currently in geomechanics and geotectonics. In this work, we conducted a series of triaxial experiments using a semipermeable separator method to form a specific composition pressure; we comparatively investigated the mechanical behaviors of sandstone in the conditions of monophase fluids CO2/N2/H2O and biphase fluid CO2‐H2O; and we analyzed the strength, elasticity modulus and brittleness of sandstones at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The early decrease in compaction rate was linked to the suppression of pressure solution creep (stress‐driven mass transfer); meanwhile, the increase was linked to an increase in subcritical microcracking. Recent results by Hu et al . confirm the strong influence of the pore fluid chemistry for sandstones.…”
Section: Alteration Of Mechanical Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…The early decrease in compaction rate was linked to the suppression of pressure solution creep (stress‐driven mass transfer); meanwhile, the increase was linked to an increase in subcritical microcracking. Recent results by Hu et al . confirm the strong influence of the pore fluid chemistry for sandstones.…”
Section: Alteration Of Mechanical Propertiesmentioning
confidence: 66%
“…The early decrease in compaction rate was linked to the suppression of pressure solution creep (stress-driven mass transfer); meanwhile, the increase was linked to an increase in subcritical microcracking. Recent results by Hu et al 167 confirm the strong influence of the pore fluid chemistry for sandstones. These changes underscore the importance of a thorough characterization of the rock lithology, morphology, and geological CO 2 storage conditions to understand the impact of CO 2 -induced geomechanical alterations on heterogeneous rocks such as sandstone.…”
Section: Static Tests On Reservoir Rock In Gcs Conditionsmentioning
confidence: 78%
“…We have already used the same cores to study the influence of the intermediate principal stress (σ 2 ) on the permeability evolution during true triaxial compression [41]. Although this paper emphasizes the effect of confining pressure (P c ) on the strain-permeability behavior of mudstone, which can be tested by a conventional triaxial apparatus with a cylindrical specimen, the true triaxial apparatus for rocks [41][42][43][44][45] at the Institute of Rock and Soil Mechanics, Chinese Academy of Sciences, which can exert three stresses independently, was still employed in this study because the specimen usually failed with a relatively flat fault parallel to σ 2 [42,[46][47][48]; the flow in the σ 2 direction can still be regarded as a one-dimensional flow. In contrast, the fault of the specimen in the CTC is not only very rough but also oblique to the flow direction [40,49] and the fluid flow inside the specimen near or after failure cannot be approximated as a one-dimensional flow; therefore, the cores in this study were also processed into cuboid specimens of 5 cm square by 10 cm long ( Figure 1) and the permeability in the σ 2 direction was monitored during deviatoric loading.…”
Section: Specimen Apparatus and Experimental Proceduresmentioning
confidence: 99%
“…The observed effects may be extended to the compaction creep of sandstones, when subcritical crack growth controls deformation. Previous workers have shown that microcracking is an important mechanism in sandstone deformation high stresses and strains (Heap et al, ; J. Zhang et al, ) and the presence of water leads to a pronounced weakening effect (Baud et al, ; Hu et al, , ). This suggests that, compared to the behavior of quartz sands, sandstones respond similarly to changes in water content and solution pH and presumably to the introduction of additives such as those studied here.…”
Section: Discussionmentioning
confidence: 99%